Usher syndrome type III (USH3) linked to chromosome 3q in an Italian family. Issue 8 (August 1998) - Gasparini, P; De Fazio, A; Croce, A I; Stanziale, P; Zelante, L
Abstract : We report an Italian family affected by Usher type III syndrome. Linkage study, performed using markers corresponding to the Usher loci already mapped, clearly showed linkage with markers on chromosome 3q24-25. Our data further support the presence of an Usher III locus on chromosome 3, as recently reported in a Finnish population.